1996
DOI: 10.1097/00005176-199607000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status in Untreated Children with Acute Leukemia as Compared with Children without Malignancy

Abstract: We evaluated the nutritional status of 173 consecutive children with newly diagnosed leukemia compared with that of 307 children with benign acute diseases. Nutritional status was assessed by anthropometric measurements including weight, height, weight for height, midarm circumference (MAC) and triceps skin-fold (TSF), and by biochemical indices, in particular prealbumin (TBPA) and retinol-binding protein (RBP). On admission, no significant differences were found between groups in weight, height, weight for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Similarly, observations on triceps skinfold thickness concurred with studies abroad whereby the mentioned index among patients with acute leukaemia not only differed significantly compared to healthy, normal children [7,19], but were also found to increase significantly post-induction chemotherapy [20]. On the other hand, there were studies which have observed no significant changes in the measurements of MUAC or triceps skinfold thickness among leukemia patients [21][22][23].…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, observations on triceps skinfold thickness concurred with studies abroad whereby the mentioned index among patients with acute leukaemia not only differed significantly compared to healthy, normal children [7,19], but were also found to increase significantly post-induction chemotherapy [20]. On the other hand, there were studies which have observed no significant changes in the measurements of MUAC or triceps skinfold thickness among leukemia patients [21][22][23].…”
Section: Discussionsupporting
confidence: 74%
“…The proportion of undernourished children with ALL varies from nearly 10% in the developed nations [2,3] to more than 60% in the developing countries [4][5][6]. Low folate and B12 levels are common in Indian children [7], and lower levels in children with ALL has been earlier reported [8].…”
mentioning
confidence: 99%
“…It may also be due to increased metabolic demand, associated vomiting, decreased absorption and excessive loss from diarrhea as well as inadequate intake due to mechanical obstruction from head and neck and gastrointestinal tumors [25]. The effect of cancer on nutrition is dependent on the stage of the tumor as it has been observed that the prevalence of malnutrition in newly diagnosed cancer patients is not different from that in the reference population or in children with benign tumors [26]. However, with advancement in stage and the consequent catabolic effect of the tumor, cancer patients may be more predisposed to malnutrition.…”
Section: Discussionmentioning
confidence: 99%